Ustava Republike Slovenije = Constitution of the Republic of Slovenia Dvojezična izdaja = Bilingual edition (Pamflet, 2022)
This edition of the Constitution of the Republic of Slovenia is accompanied by photographs taken on 19 June 2020, when during a wave of protests in defence of democracy, a group of citizens decided to make a symbolic gesture - to read the Slovenian Constitution in front of the National Assembly building. The response of the authorities confirmed that the democratic rights guaranteed by the Constitution are indeed threatened.